Robots : what everyone needs to know - Husbands, Phil (New York : Oxford University Press, 2021)
"This book presents a balanced and broad introduction to robotics and the current state of the field, analyzing where it has come from and where it might go in the future. Beginning with the history of robotics and its complex relationship with popular culture, it then moves on to discuss the technology underlying robots, exploring the limits of what robots can actually do now and what they might be able to do in the future. Naturally, these machines, which often seem to display life-like properties, are attracting great attention. Do they pose a threat or an unprecedented opportunity? Will they replace traditionally human workforces-as indeed they have in some sectors already? And although the "singularity" may not be something to worry about, there are certainly ethical issues needing consideration as robots with some intelligence are increasingly used. The book considers both these ethical problems and also the wider socio-political challenges that robots are already creating, and the larger ones they might bring in the future"--
Includes bibliographical references and index.
Keywords: Robotics -- Popular works; Robots -- Moral and ethical aspects -- Popular works; Robots -- Forecasting